Institutional Morality, Authority, and Ethics Committees: How Far Should Respect for Institutional Morality Go? - Loewy, Erich H. (Cambridge quarterly of healthcare ethics, 1994)
Virtually all persons who have had a hand in shaping the concept of ethics committees in this country accept the principle that the individuals making up the ethics committee should represent different interests, backgrounds, and viewpoints. In other words, ethics committees are intended mainly to represent the interests of the communities they serve. However, ethics committees often also serve hospitals that are religiously based and who, not unreasonably, may insist on affirming their own institutional morality and their own peculiar way of looking at some problems. Deep-seated ethical quandaries, especially in shaping policy, are often unavoidable.